The UFAW handbook on the care and management of laboratory and other research animals - Biswas, Kanishka; Golledge, Huw (Hoboken, New Jersey John Wiley & Sons, Ltd., 2024)
" The latest edition of the seminal reference on the care and management of laboratory and research animals. The newly revised ninth edition of The UFAW Handbook on the Care and Management of Laboratory and Other Research Animals delivers an up-to-date and authoritative exploration on worldwide developments, current thinking, and best practices in the field of laboratory animal welfare science and technology. The gold standard in laboratory and captive animal care and management references, this latest edition continues the series’ tradition of excellence by including brand-new chapters on ethical review, the care of aged animals, and fresh guidance on the care of mole rats, corvids, zebrafish, and decapods. The book offers introductory chapters covering a variety of areas of laboratory animal use, as well as chapters on the management and care of over 30 different taxa of animals commonly utilised in scientific procedures and research around the world. It also provides: a thorough introduction to the design of animal experiments, laboratory animal genetics, and the phenotyping of genetically modified mice, comprehensive explorations of animal welfare assessment and the ethical review process, practical discussions of legislation and oversight of the conduct of research using animals from a global perspective, in-depth examinations of the planning, design, and construction of efficient animal facilities, special housing arrangements, and nutrition, feeding, and animal welfare. The UFAW Handbook on the Care and Management of Laboratory and Other Research Animals Ninth Edition is essential for laboratory animal scientists, veterinarians, animal care staff, animal care regulatory authorities, legislators, and professionals working in animal welfare non-governmental organizations. "
Includes bibliographical references and index.
Keywords: Veterinary Medicine